Study Of structural Behaviour And Residual Drift Of Concrete frames Reinforced With Shape Memory Alloy Rebar - Masoud Mirtaheri (Iranian Society of Structrual Engineering (ISSE), 2019)
Buildings in high seismic regions are prone to severe damage and collapse during earthquakes due to large lateral deformations. The use of superelastic shape memory alloys (SMAs) as reinforcements in concrete structures is gradually gaining interest among researchers. the effect of SMAs as reinforcement in concrete structures is analytically investigated for 3, 6 and 8-story reinforced concrete (RC) buildings. Each building has ﬁve bays in both directions with the same bay length of 5m. For each concrete building, three different reinforcement details are considered: (1) steel reinforcement (Steel), (2) SMA bar used in the plastic hinge region of the beams and steel bar in other regions (Steel-SMA), and (3), beams fully reinforced with SMA bar (SMA) and steel bar in other regions. For each case, columns are reinforced with steel bar. Results obtained from the analyses indicate that the value of Sa in Steel-SMA frames are higher than SMA frames, and its recovery capacity is almost similar with SMA frames. the SMAs materials are expensive, and the use of Steel-SMA frames can be reasonably effective in seismic zones. The comparison between frames with various reinforcements details shows that Sa of 3-story frames with various reinforcements are almost identical. but, in 6- and 8-story frames, Sa of Steel frames are higher than others. frames with SMA bars in the all length or plastic hinge region of the beam have reached a same level of seismic demand under lower spectral acceleration which can be resulted from the decreased stiffness caused by SMA bars. results indicate that structural behaviour factor in 3 and 6 story buildings with different types of reinforcement is not much change, but this change is perceptible in the 8-story frame. In the case of residual drift in all cases, the use of shape memory alloys will reduce this drifts.